2005
DOI: 10.1128/jvi.79.9.5752-5761.2005
|View full text |Cite
|
Sign up to set email alerts
|

Coat Protein Activation of Alfalfa Mosaic Virus Replication Is Concentration Dependent

Abstract: Alfalfa mosaic virus (AMV) and ilarvirusRNA-protein interactions play important roles in a variety of biological processes and are of particular importance in the life cycle of positive-strand RNA viruses, where the genomic RNA serves as the template for protein synthesis and replication. Alfalfa mosaic virus (AMV) and ilarviruses provide an interesting model system in which to study RNA-protein interactions because the viral coat protein (CP) has multiple roles in the viral life cycle, not all of which are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 47 publications
(65 reference statements)
1
23
0
Order By: Relevance
“…In addition, CP has been reported to regulate RNA replication in other plant viruses. For example, RNA replication of Alfalfa mosaic virus (AMV) was strongly stimulated at low CP concentrations but progressively decreased at higher concentrations (9). In the protoplast assay, we found that CP deletion in BaMV significantly decreased genomic RNA accumulation.…”
Section: Discussionmentioning
confidence: 77%
“…In addition, CP has been reported to regulate RNA replication in other plant viruses. For example, RNA replication of Alfalfa mosaic virus (AMV) was strongly stimulated at low CP concentrations but progressively decreased at higher concentrations (9). In the protoplast assay, we found that CP deletion in BaMV significantly decreased genomic RNA accumulation.…”
Section: Discussionmentioning
confidence: 77%
“…We propose that the differences in functional data from the two laboratories may be traced to the use of wild-type cells (described here) versus in vitro analysis and the use of transgenic cells that overexpress replicase proteins (22). The accumulated evidence presented here, along with functional data presented in the accompanying paper (12) and the crystal structure of the AMV RNA-peptide complex (11), suggest that CP binding organizes the 3Ј termini of the viral RNAs for activation of early viral RNA replication.…”
mentioning
confidence: 99%
“…Neeleman et al (36) reported that the coat protein (CP) of alfalfa mosaic virus (AMV), a member of the genus Alfamovirus in the family Bromoviridae, can bind to the 3= end of viral RNA and enhance subgenomic RNA4 translation. The AMV CP can regulate RNA synthesis by binding to the 3= ends of Alfamovirus and Ilarvirus RNAs to activate genome replication (6,23). In rotavirus, VP2 can serve as a scaffold for the viral polymerase as well as act as a cofactor for VP1 to initiate genome replication (32,38).…”
Section: R E T R a C T E Dmentioning
confidence: 99%